2010
DOI: 10.1002/jbmr.176
|View full text |Cite
|
Sign up to set email alerts
|

Calcium supplementation and the risks of atherosclerotic vascular disease in older women: Results of a 5-year RCT and a 4.5-year follow-up

Abstract: Concern has been expressed that calcium supplementation, a key intervention for preventing osteoporotic fracture in older women, may increase the risk of atherosclerotic vascular disease. To evaluate the risk further, an examination of complete verified atherosclerotic vascular hospitalization and mortality data from a 5-year randomized, controlled trial (RCT) of calcium carbonate and 4.5 years of posttrial follow-up was undertaken. This study used data from a published 5-year randomized, double-blinded, place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
130
3
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(142 citation statements)
references
References 29 publications
2
130
3
7
Order By: Relevance
“…The regular monthly follow-ups allowed close monitoring of protocol adherence and further counselling to ensure adherence to the trial protocol. We observed a high compliance of 85 % to Ca supplements, whereas comparable trials reported compliance rates between 59 and 85 % (6,16,(53)(54)(55) . We also observed that the rigorous design of our pilot trial was effective to help achieve the target dietary Ca in each group at monthly follow-ups.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The regular monthly follow-ups allowed close monitoring of protocol adherence and further counselling to ensure adherence to the trial protocol. We observed a high compliance of 85 % to Ca supplements, whereas comparable trials reported compliance rates between 59 and 85 % (6,16,(53)(54)(55) . We also observed that the rigorous design of our pilot trial was effective to help achieve the target dietary Ca in each group at monthly follow-ups.…”
Section: Discussionmentioning
confidence: 53%
“…cardiovascular events (15)(16)(17)(18) . On the other hand, most studies demonstrated that dietary sources of Ca have not been linked with cardiovascular adverse events (13,19,20) or have been shown to be favourable to cardiovascular health (21)(22)(23)(24) .…”
mentioning
confidence: 99%
“…On the other hand, the possibility that excessive intake of calcium can lead to an increased risk of myocardial infarction and/or ischemic brain lesions has been repeatedly highlighted in the literature. [5][6][7] The absorption of calcium is more regular when we use calcium via the diet regard to calcium via the supplemen- Dietary calcium intake in elderly patients with osteoporosis tation. 8 Calcium intake via the diet reduces considerably the possibility of a transient rise in serum calcium levels that many authors consider the main cause of the increased risk of vascular calcifications.…”
Section: Discussionmentioning
confidence: 99%
“…According to Reid and colleagues [3], such trials cannot be envisaged for reasons of practicality and ethical obstacles. But there is one such study, and it showed no negative cardiovascular effects [7].…”
mentioning
confidence: 99%